EXPLORING THE ROLE OF GENDER IN MSME ENTREPRENEURSHIP DYNAMICS: STRUCTURAL IMPLICATIONS FOR INCLUSIVE AND SUSTAINABLE BUSINESS GROWTH IN THE CONTEXT OF THE DIGITAL ECONOMY - Manafe, Mesri Welhelmina Nisriani; Fanggidae, Herny Constantia (Technopreneurship and Educational Development Review (TENDER), 2025)
This research aims to explore the role of gender in the entrepreneurial dynamics of Micro, Small and Medium Enterprises (MSMEs) and its structural implications for inclusive and sustainable business growth in the context of the digital economy. Using a qualitative approach through a literature review method, this study analyses 22 selected scientific articles published between 2002 and 2025 and obtained from Google Scholar and other credible online sources. The analysis shows that gender inequality is still a structural issue that affects women's access to digital technology, financing, business networks, and entrepreneurship training. In the context of the digital economy, women MSME actors often face additional barriers due to social norms, multiple domestic responsibilities, and limited digital literacy. These findings are supported by Gender Role Theory, Institutional Theory, and Digital Divide, which explain the complex relationship between social structures, policies, and technology adoption. The study concludes that inclusive and sustainable business growth will not be achieved without gender mainstreaming in MSME digital transformation policies.